The Predictive Effect of Technology Follow-up and Professional Competence on Job Satisfaction of Physical Education Teachers - Nurullah Çelik; Oğuzhan Yıldız; Şeyma Aksu (Pamukkale University, 2024)
The study aimed to determine the predictive effect of technology follow-up and professional competence on the job satisfaction levels of physical education teachers. A correlational survey was used in the study. The study sample consists of 217 physical education teachers. Participants in the study were determined by the convenience sampling method. To collect data, the "Personal Information Form," "Teachers Self-Efficacy Scale," and "Job Satisfaction Scale" were used in the study. Descriptive statistics, Pearson correlation analysis, and hierarchical regression analysis were used for analysis. According to the results, a significant positive relationship was found between the frequency of technology follow-up and job satisfaction (r = .230, β = .25, p